Correction: Issaoui et al. Geometric Characterization of the Mateur Plain in Northern Tunisia Using Vertical Electrical Sounding and Remote Sensing Techniques. ISPRS Int. J. Geo-Inf. 2024, 13, 333 - Wissal Issaoui; Imen Hamdi Nasr; Dimitrios D. Alexakis; Wafa Bejaoui; Ismael M. Ibraheem; Ahmed Ezzine; Dhouha Ben Othman; Mohamed Hédi Inoubli (ISPRS International Journal of Geo-Information)
There was an error in the original publication [...]